Treatment strategies for Lennox-Gastaut syndrome: outcomes of multimodal treatment approaches - Ji-Hoon Na; Da Eun Jung; Hee Jung Kang; Hoon-Chul Kang; Heung Dong Kim (Therapeutic Advances in Neurological Disorders, 2022)
Background: Multimodal treatment approaches are often considered for patients with Lennox-Gastaut syndrome (LGS). Creating an algorithm that can guide healthcare providers in selecting treatment options for patients with LGS remains a challenge. Herein, we assessed the long-term seizure-free and neurodevelopmental outcomes of stepwise multimodal treatment in patients with LGS. Objective: Herein, we assess the long-term seizure-free and neurodevelopmental outcomes of stepwise multimodal treatment in patients with LGS. Methods: We retrospectively examined the data of 371 patients with LGS who underwent stepwise multimodal treatment, including antiseizure medication (ASM) therapy, dietary therapy (DT), resective epilepsy surgery (R-ES), and palliative epilepsy surgery (P-ES). The seizure-free outcome was considered to be the effect of the final treatment according to the treatment algorithm, and the percentage of patients who remained seizure-free in each treatment group was calculated. ASM treatment, DT, R-ES, and P-ES were applied to 371 (100%), 201 (54.2%), 112 (30.2%), and 115 (31.0%) patients with LGS, respectively. We evaluated the stepwise multimodal treatment outcomes in these patients. Results: One hundred sixty-eight patients (45.3%) remained seizure-free for at least 1 year (seizure-free-for-1-year group), 61 of whom (16.5%) remained seizure-free for more than 5 years (remained-seizure-free group). Among the patients treated with ASM therapy, DT, R-ES, and P-ES, 41 (11.1%), 53 (14.3%), 56 (15.1%), and 29 (7.8%), respectively, remained seizure-free for 1 year. In addition, 15 (4.1%), 15 (4.1%), 19 (5.1%), and 12 (3.2%) patients in the ASM, DT, R-ES, and P-ES treatment groups, respectively, remained seizure-free for more than 5 years. Both the seizure-free-for-1-year and remained-seizure-free groups showed significant improvement in electroencephalography findings and neurodevelopmental status following treatment. Conclusion: This study provides an update on the long-term seizure outcomes and neurodevelopmental improvements in a large cohort of patients with LGS following comprehensive multimodal treatment. We emphasize that the active combination of multiple ASMs, DT, and surgical treatment could provide long-term seizure-free outcomes and significant neurological benefits to patients with LGS.